Online and offline hybrid teaching system based on virtual reality - Yu, Hou; Zulkifli, Nurul Nadwa; Khairuddin, Nozieana (Multidisciplinary Digital Publishing Institute, 2024)
We describe in this article the current development status of virtual reality (VR) technology and its application prospects in education, and we describe the design and implementation process for a hybrid online and offline teaching system. This system utilizes VR devices and software to bring students into a virtual learning environment, to interact with virtual objects, and to perform practical operations. At the same time, the system provides online courses, learning resources, and social platforms to promote cooperation and communication among students. Compared with traditional teaching, this online and offline hybrid teaching system significantly improves students’ learning interest and induces active participation. Students have positive experiences of using VR technology for learning and believe that the system provides rich and practical learning resources.